Nitrodĕlozní růstová retardace plodu a tĕhotenství - Burnog, T (Ceska gynekologie, 1996)
IUGR (intrauterine growth retardation) is a serious complication of pregnancy. The author compared in the submitted paper different diagnostic and therapeutic possibilities in a six-year retrospective group of 181 hypotrophic foetuses. Based on the results he emphasizes the necessity of magnesiotherapy and prevention of IUGR by acylpyrin. It is impossible to monitor and treat adequately a pregnant woman with a hypotrophic foetus without Doppler sonography. Combination of indexes from various areas (brain, umbilicus) is useful. Even the somewhat obsolete method of assessment of estriol in the urine of pregnant women should not be refuted. Even during the present period of transformation of health services IUGR therapy under ambulatory conditions is not recommended. The author emphasizes the comprehensive character of evaluation of all diagnostic methods for the detection of IUGR.
Keywords: novorozenec; Infant, Newborn; Female; Fetal Growth Retardation; výsledek těhotenství; Pregnancy; Humans; ženské pohlaví; Pregnancy Outcome; lidé; růstová retardace plodu; těhotenství